Fan`s perspective on professional leagues and sporting events during COVID-19 confinement period - Vegara-Ferri, J. M.; Carboneros, M.; Deliautaite, K.; Diaz-Suárez, A.; López-Gullón, J. M. (Journal of Human Sport & Exercise, 2020)
The restriction imposed by COVID-19 pandemic has caused a great social change in the world and has affected many sectors, including the sport industry by having an impact and altering the normal development of the sport competitions and events. Therefore, it is fundamental to know sport fans` opinions about the professional championships during the confinement period. The sample is composed by 1025 professional sports leagues fans and major sporting events celebrated in Spain, with people in the age range 18-70. The instrument used to collect data was an adaptation of the American questionnaire designed by Seton Hall University. The results show that 55% of fans thought that sport leagues and events were cancelled on time. Furthermore, 92.8% of the survey respondents would not attend a live match without social distancing measures or without the existence of a vaccine; 67.4% would follow it through mass media resources with the same interest. The population group under 25 feels safe attending sports leagues or events (9.7%). These results might help to take decisions based on preventive measures to guarantee security within the sport context.